5-3x=x+5-4x

Simple and best practice solution for 5-3x=x+5-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3x=x+5-4x equation:


Simplifying
5 + -3x = x + 5 + -4x

Reorder the terms:
5 + -3x = 5 + x + -4x

Combine like terms: x + -4x = -3x
5 + -3x = 5 + -3x

Add '-5' to each side of the equation.
5 + -5 + -3x = 5 + -5 + -3x

Combine like terms: 5 + -5 = 0
0 + -3x = 5 + -5 + -3x
-3x = 5 + -5 + -3x

Combine like terms: 5 + -5 = 0
-3x = 0 + -3x
-3x = -3x

Add '3x' to each side of the equation.
-3x + 3x = -3x + 3x

Combine like terms: -3x + 3x = 0
0 = -3x + 3x

Combine like terms: -3x + 3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7f-f+3g+15= | | 13.5/1.5 | | 1-n-3n=-15 | | 6x+7(x-7)=16 | | 8y+168=x | | 15y+x= | | 3a-3=-a+5 | | 8-3(4x-1)=49 | | 10b-2b=8 | | D-17=31 | | 18+128x^2=0 | | -(7)-y=-8 | | .75x-.68x=.4 | | 0=3x^2-23x+30 | | -2÷-4/5 | | 10-6x=-4x+4 | | 2msquared+16=10m | | n/1.5=9 | | X^4+x^3-27x^2-3x-90=0 | | -4(3x-9)=8(-8-x) | | (-5x)+(-215)-(5x)+(21.5)= | | 3(3x-3)+2x=0 | | $200,000-1/10 | | 12-x=-38 | | 7x+4=4x+2 | | 9(-7)+8y=17 | | X+9y=-26 | | 2(x+4)=88 | | 3k+18=k+18 | | 168+8y=7x | | -34=v+5v-42 | | 18z+-14z-8=-30-6 |

Equations solver categories